Ergonomic space design in enhancing perceived work performance in green office building / Abdallah Muhamed Bashir - Abdallah, Muhamed Bashir (2017)
Green Building industry has been growing rapidly at the recent time due its massive engorgement to develop sustainable environment. Sustainability has become the most drive factor for economic and social benefits. Therefore, companies and organisations started to pay prominent awareness to establish green building strategies within their premises. A certified green building usually receives more attention on energy consumption, indoor environment quality, sustainable materials and so on. However, in this new world of business, employees are exposed to alternative factors within their work places that can affect their work performance and productivity. Since employees spent about 8 hours average in daily basis indoor, it is important to consider ergonomics elements of their workplace. In the light of this research, the main objectives of this research are to study and identify ergonomics space design elements in office green building. Also, the study aims to investigate employee's satisfaction with their office ergonomics space design, IEQ and perceived ergonomics impact on work performance. The outline aims used to achieve these objectives is mixed mode approach of qualitative and quantitative analysis such as questionnaires survey, empirical measurement, interviews and observations. Nevertheless, this research has identified ergonomics space design elements in existing case study and findings showed that employees were satisfied about their workplace space design, IEQ and ergonomics due to good green practices. Finding on perceived ergonomic impact on work performance showed that office ergonomics believed to enhance work performance. The research concludes the important of green ergonomics and recommends optimising ergonomics features in green office building.